HUBUNGAN KEAKTIFAN BERORGANISASI DENGAN PENGEMBANGAN SOFT SKILLS PADA MAHASISWA FAKULTAS VOKASI UNIVERSITAS AIRLANGGA - Laras Muhfidatul F. D. R; Roro Dinda S. P.; Bening Rachma Y.; Nabillah Khoirunnisa (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
Students are agents of social change who have the potential to develop science and culture also advance the nation. Students have a role that is not only limited to academic achievement, but also to personal development that involves improving social, emotional, and professional skills. One of the key aspects in realizing the formation of student capabilities is through the development of soft skills. Soft skills are a series of non-technical skills in individuals that can be honed through practice and experience. Soft skills include communication skills, adapting, managing time and emotions, and problem solving. Soft skills development in students can be done through various activities, one of which is involvement in organizations. An organization is a group of individuals who have the same goals and collectively achieve them. In a series of organizational activities, it is inseparable from the application of non-technical skills, so that the organization is one of the platforms in honing and developing soft skills. This study aims to determine the relationship between organizational activeness and soft skills development in students of the Faculty of Vocational Studies, Universitas Airlangga. The approach used, namely quantitative correlation with a sample consisting of 110 students who are active in the organization. Data were collected through questionnaires and literature studies. Data analysis used SPSS with validity, reliability, normality, linearity, and Pearson Correlation tests. The results showed that organizational activity has a significant relationship with the development of soft skills in students of the Faculty of Vocational Studies, Universitas Airlangga. The Pearson Correlation test using SPSS version 30.00 resulted in a significance value of 0.000 <0.05 and a Pearson Correlation of 0.849, which shows a very strong relationship between the two variables, in accordance with the correlation guidelines of 0.80-1.000.